The Predictive Value of Estrogen Receptor 1 on Adjuvant Chemotherapy in Locally Advanced Colorectal Cancer: A Retrospective Analysis With Independent Validation and Its Potential Mechanism - Ye, Shu-Biao; Cheng, Yi-Kan; Deng, Ru; Deng, Yanhong; Li, Peisi; Zhang, Lin; Lan, Ping (Frontiers in Oncology, 2020)
Abstract: Purpose: To investigate the predictive biomarker value of ESR1 expression in tumor tissue on adjuvant chemotherapy in curatively resected colorectal cancer (CRC). Methods: A total of 467 CRC patients in 2007-2010 were retrospectively evaluated. Clinical information and follow-up data were retrieved from hospital registries and patient files. What’s more, we used an external independent cohort (n=511) from GSE39582 for further validation. Overall survival was estimated by the Kaplan-Meier method and the survival curves compared by the log-rank tests. Cox proportional hazards model were used for multivariate analyses to calculate the hazard ratios (HR) and test independent significance. Immunohistochemistry and Western blot were applied to detect protein expression of ESR1 in CRC patients and cell lines. The stable knockdown and overexpressed cells were transduced with the lentivirus. Cell viability was measured by MTS reagent. Results: The predictive value of ESR1 was investigated in locally advanced CRC patients. Kaplan-Meier analysis indicated that ESR1 expression was significantly correlated with OS in patients receiving adjuvant chemotherapy from these cohorts, with p value =0.015 and p<0.001, respectively. ESR1 expression was significantly correlated with 5FU-based adjuvant chemotherapy in training with HR of 1.792 (95%CI: 1.100-2.921, p=0.019). Downregulation of ESR1 was related with enhanced chemosensitivity to 5-flurouracil (5-FU) in CRC cell lines, while upregulation of ESR1 was correlated with decreased chemosensitivity. Conclusions: The present study manifest clinical validity of ESR1 expression as a predictive biomarker on 5FU based adjuvant chemotherapy in stage II-III CRC.